ZBTB2 links p53 deficiency to HIF-1-mediated hypoxia signaling to promote cancer aggressiveness - Koyasu, S; Horita, S; Saito, K; Kobayashi, M; Ishikita, H; Chow, CC; Kambe, G; Nishikawa, S; Menju, T; Morinibu, A; Okochi, Y; Tabuchi, Y; et al. (EMBO Press, 2022)
Aberrant activation of the hypoxia-inducible transcription factor HIF-1 and dysfunction of the tumor suppressor p53 have been reported to induce malignant phenotypes and therapy resistance of cancers. However, their mechanistic and functional relationship remains largely unknown. Here, we reveal a mechanism by which p53 deficiency triggers the activation of HIF-1-dependent hypoxia signaling and identify zinc finger and BTB domain-containing protein 2 (ZBTB2) as an important mediator. ZBTB2 forms homodimers via its N-terminus region and increases the transactivation activity of HIF-1 only when functional p53 is absent. The ZBTB2 homodimer facilitates invasion, distant metastasis, and growth of p53-deficient, but not p53-proficient, cancers. The intratumoral expression levels of ZBTB2 are associated with poor prognosis in lung cancer patients. ZBTB2 N-terminus-mimetic polypeptides competitively inhibit ZBTB2 homodimerization and significantly suppress the ZBTB2-HIF-1 axis, leading to antitumor effects. Our data reveal an important link between aberrant activation of hypoxia signaling and loss of a tumor suppressor and provide a rationale for targeting a key mediator, ZBTB2, to suppress cancer aggressiveness.